Assessing Innovative Practices In Funding Entrepreneurship Education In Universities In Cross River State, Nigeria: Implications For Sustainable National Development - Akuegwu, B. A.; Uche, K. K.; Udo, D. E. (Advances in Social Sciences Research Journal, 2018)
This study assessed innovative practices in funding entrepreneurship education in universities in Cross River State, Nigeria and their implications for sustainable national development. Two research questions and one hypothesis were isolated to give direction to this investigation. Mixed methods research involving qualitative and quantitative techniques were adopted. 110 programme managers in the two universities constituted the population. All of them where used as sample. 13 innovative practices in funding entrepreneurship education were identified through interview involving programme managers. These innovative practices guided the researchers to construct an instrument titled “Innovative Practices in Funding Entrepreneurship Education Questionnaire (IPFEEQ)” which was used for data collection. Data collected were analysed statistically using Descriptive Statistics (Mean Rating) and Independent t-test statistical techniques. Results obtained indicated that entrepreneurship education programme managers have innovative practices with which they utilize in funding entrepreneurship education; programme managers are most effective in using marketing of products as innovative practice in funding entrepreneurship education. Ownership of universities does not significantly influence the utilization of innovative practices in funding entrepreneurship education. It was concluded that more efforts should be geared towards ensuring the success of innovative practices in funding entrepreneurship education given its efficacy in providing alternative funding.